Evaluation of biochemical and electrolytic components of semen from ram supplemented with different concentrations of selenium and its correlation with sperm quality - Silva, D. C. [UNESP]; Codognoto, V. M. [UNESP]; Piagentini, M. [UNESP]; Dantas, A. [UNESP]; Sousa, G. C. [UNESP]; Silva, L. S. [UNESP]; Souza, E. R. [UNESP]; Filho, R. A. Almeida [UNESP]; Denadai, R. [UNESP]; Oba, E. [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of the study was to evaluate whether supplementation with different levels of selenium (Se) can change the biochemical and electrolytic components of semen, causing an improvement in seminal quality in rams. Thirty animals were kept in an intensive pen system, fed with hay and commercial ration, allocated into five groups (six animals/pen) and supplemented with a mineral mixture containing 0mg (G1), 5mg (G2), 10mg (G3), 15mg (G4) and 20mg (G5) of Se/kg. Each group received a different treatment every 56 days and treatments were rotated between groups following a dynamic sequence. Semen samples were collected by electroejaculation after the end of each treatment to evaluate the levels of fructose, citric acid, potassium (K), sodium (Na), calcium (Ca), Se, zinc (Zn), manganese (Mn), sulfur (S) and lead (Pb). The statistical design was a 5x5 Latin square. The different levels of Se supplementation evaluated maintained the concentrations of electrolytes and minerals in the semen at the required levels and did not change the sperm quality, concluding that higher intakes of Se do not cause antagonistic effects on the absorption and subsequent action of other essential minerals supplied to the animals and still maintains electrolyte balance
Avaliação de componentes bioquímicos e eletrolíticos do sêmen de ovinos suplementados com diferentes concentrações de selênio e sua correlação com a qualidade espermática
Keywords: Ejaculate; Micromineral; Ovine; Supplementation